GLS1 Mutant Mice Display Moderate Alterations of Hippocampal Glutamatergic Neurotransmission Associated with Specific Adaptive Behavioral Changes. (1st January 2019) - Dutar, Patrick; Tolle, Virginie; Kervern, Myriam; Carcenac, Carole; Carola, Valeria; Gross, Cornelius; Savasta, Marc; Darmon, Michèle; Masson, Justine
Highlights: GLS1 depletion induces moderate impairment of synaptic plasticity. Lower brain glutamate does not alter mnesic performances in GLS1 mutant mice. Hypoglutamatergic state causes moderate changes in depressive-like behavior. Lower brain glutamate does not alter response to acute stress. Abstract: Significant alterations in glutamatergic neurotransmission have been reported in major depressive disorder (MDD) that could underlie psychiatric traits. Studies were mainly interested in synaptic dysfunction in the prefrontal cortex, a key structure involved in depressive-like behavior, however hippocampus has been shown to be important in MDD. As cognitive deficits such as hippocampus-memory process were observed in MDD, we investigated in a mild hypoglutamatergic model behaviors related to depression and memory, synaptic transmission parameters and glutamatergic state specifically in the hippocampus. We thus characterized these phenotypes in adult male mice partially depleted in glutaminase type 1 or GLS1 (GLS1 HET), the enzyme responsible for glutamate synthesis in neurons, that we previously characterized as displaying moderate lower levels of glutamate in brain. We showed that GLS1 mutant mice display AMPA-R-mediated response deficits after prolonged repetitive stimulation with electrophysiological recording and inability to sustain glutamate release by microdialysis experiments with no consequences on behavioral spatial learning performances. However, their ability to escape from unpleasant but repeated escapable condition was attenuated whereas they were more immobile in the unescapable situation in the FST during re-test. These results show that GLS1 mutant mice display moderate impairments of hippocampal glutamatergic neurotransmission and moderate changes in adaptive behaviors that have been shown to participate to the development of depressive-like state.